Stepwise establishment of functional microbial groups in the infant gut between 6 months and 2 years: A prospective cohort study - Pham, Van T.; Greppi, Anna; Chassard, Christophe; Braegger, Christian; Lacroix, Christophe (Frontiers in Nutrition, 2022)
The early intestinal colonization of functional microbial groups plays an essential role on infant gut health, with most studies targeting the initial colonization period from birth to 6 months of age. In a previous report, we demonstrated the metabolic cross-feeding of lactate and identified keystone species specified for lactate utilization in fecal samples of 40 healthy infants. We present here the extension of our longitudinal study for the period from 6 months to 2 years, with focus on colonization of functional groups involved in lactate metabolism and butyrate production. We captured the dynamic changes of the gut microbiota and reported a switch in the predominant lactate-producing and lactate-utilizing bacteria, from Veillonella producing propionate in the first year to Anaerobutyrycum hallii producing butyrate in the second year of life. The significant increase of butyrate producers and fecal butyrate concentration was also pinpointed to the weaning period between 6 and 10 months. Correlation analyses further suggested, for the first time, the metabolic cross-feeding of hydrogen in infants. In conclusion, our longitudinal study in 40 Swiss infants provides important insights into the colonization of functional groups involved in lactate metabolism and butyrate production in the first 2 years of life.